2017
DOI: 10.1016/j.carbpol.2017.05.089
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene cellulose nanofibrils nanocomposites

Abstract: This paper investigates the use of an aqueous dispersion of polyethylene copolymer with a relatively high content of acrylic acid as a compatibilizer and as an alternative medium to obtain polyethylene CNF nanocomposites. The CNF content was varied from 1 to 90wt% and the appearance, optical, thermal, mechanical and rheological properties, as well the morphology of the films were evaluated. The PE/CNF films are transparent up to 20wt% of NFC indicating a good dispersion of CNF, but a poor distribution, with PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…This threshold concentration has been reported earlier in similar composites, Larsson et al reported a significant stiffness increase in CNF/PLA composites at a cellulose concentration of 25 wt% (Larsson et al 2012). Moreover, Maia et al reported a doubling of the stiffness to 0.67 GPa in the interval 20-30 wt% for CNF and elastomer composites (Maia et al 2017). The strength r b of the CNF composites was also affected by this concentration threshold (Fig.…”
Section: Tensile Propertiesmentioning
confidence: 48%
See 2 more Smart Citations
“…This threshold concentration has been reported earlier in similar composites, Larsson et al reported a significant stiffness increase in CNF/PLA composites at a cellulose concentration of 25 wt% (Larsson et al 2012). Moreover, Maia et al reported a doubling of the stiffness to 0.67 GPa in the interval 20-30 wt% for CNF and elastomer composites (Maia et al 2017). The strength r b of the CNF composites was also affected by this concentration threshold (Fig.…”
Section: Tensile Propertiesmentioning
confidence: 48%
“…However, addition of cellulose to EAA did not significantly influence the primary crystallinity of EAA (X c2 in Table 2), which varied between 9 and 15% for the composite materials with no apparent trend. Previous works on cellulose composites have shown that cellulose reinforcement in composites can both induce and reduce crystallinity in the matrix phase (Samir et al 2004;Yao et al 2008;Maia et al 2017). The crystallinity of EAA does not significantly change with the addition of cellulose, apart from a small reduction in crystallinity at higher cellulose contents, which suggests that any improvement in mechanical properties of the composites would probably be the result of the cellulose reinforcement and not due to the increased crystallinity of the EAA.…”
Section: Thermal Propertiesmentioning
confidence: 73%
See 1 more Smart Citation
“…Improved mechanical properties were achieved with an increase in the Young's modulus. The rheological behavior indicated good melt processability [113].…”
Section: Properties and Potential Applicationsmentioning
confidence: 95%
“…The use of an aqueous dispersion of polyethylene copolymer with a relatively high content of acrylic acid as a compatibilizer and as an alternative medium to obtain polyethylene NFC nanocomposites was a matter of recent study [113]. The NFC content was varied from 1 to 90 wt%, and the appearance, optical, thermal, mechanical and rheological properties, as well the morphology of the films, were evaluated.…”
Section: Properties and Potential Applicationsmentioning
confidence: 99%